2019
DOI: 10.3390/jcs3040109
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Carbon Nanotubes Enhanced Structural Composites with Improved Toughness and Damage Monitoring

Abstract: The potential of carbon nanotubes (CNT) as multifunctional filler in poly(epoxy)-based structural composites has been investigated. In a first step the reinforcement effect of CNT has been studied by tensile and three points bending tests, which evidenced significant improvements of stress and strain at break (respectively +17% and +30% for tensile tests on unidirectional carbon fibre-epoxy composites). Moreover, fracture experiments have also revealed a positive effect of CNT on the toughness (G1c) of carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…The electron transfer is greatly improved at the closest conductive areas between the carbon fibers' layers. In a CNT network, the main conduction mode is tunneling conductivity, 42–44 that explains the logarithmic relationship between conductivity and CNT loading, as the latter directly influences the minimal interparticle distance between the CNT 45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron transfer is greatly improved at the closest conductive areas between the carbon fibers' layers. In a CNT network, the main conduction mode is tunneling conductivity, 42–44 that explains the logarithmic relationship between conductivity and CNT loading, as the latter directly influences the minimal interparticle distance between the CNT 45 …”
Section: Resultsmentioning
confidence: 99%
“…In a CNT network, the main conduction mode is tunneling conductivity, [42][43][44] that explains the logarithmic relationship between conductivity and CNT loading, as the latter directly influences the minimal interparticle distance between the CNT. 45 Allaoui and Zeng 14,41 studies reported that the CNT percolation threshold ranged from 0.5 to 2.5 wt%. In fact, the uniformity and dispersion of the CNT can significantly influence the percolation threshold.…”
Section: Through-thickness Electrical Conductivitymentioning
confidence: 99%
“…Three-point bend testing was conducted on traditionally fabricated multifunctional carbon nanotubes, enhanced structural composites for improved toughness, and damage monitoring. Reinforcement effects of the multifunctional carbon nanotubes enhanced structural composites were structurally investigated via tensile and three-point bend testing, which led to significant improvement of stress and strain at failure [13]. This study also included the assessment of the structural health monitoring capability via the use of quantum resistive strain sensors made up of carbon nanotubes filled epoxy nanocomposite embedded at the core of the glass fiber-epoxy composites [13].…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcement effects of the multifunctional carbon nanotubes enhanced structural composites were structurally investigated via tensile and three-point bend testing, which led to significant improvement of stress and strain at failure [13]. This study also included the assessment of the structural health monitoring capability via the use of quantum resistive strain sensors made up of carbon nanotubes filled epoxy nanocomposite embedded at the core of the glass fiber-epoxy composites [13]. While the electrical characterization is mentioned, the electrical conductivity is not included in this research [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation